2019
DOI: 10.3329/updcj.v9i2.43733
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of age with periodontal diseases for males and females in Bangladesh; A hospital registry based cross-sectional observational study.

Abstract: Periodontal diseases are the most commonly occurred diseases in the oral cavity with a widespread distribution around the globe. Variation in periodontal tissues associated with the aging and gender of the patient. The aim of this study was to determine relationship of age with periodontal diseases for males and females in Bangladeshi people. This study was conducted on 1837 patients visiting Department of Periodontology & Oral Medicine, Update Dental College & Hospital, from January 2017 to December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of the collected specimens showed that there was no significant difference between male 33 (55.0%) and female 27 (45.0%) patients (Table 1). These results were consistent with [19] and exhibited no significant association between gender and periodontal disease. Whereas, [20] found that males had a greater frequency of periodontal diseases due to worse oral hygiene than female subjects.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The results of the collected specimens showed that there was no significant difference between male 33 (55.0%) and female 27 (45.0%) patients (Table 1). These results were consistent with [19] and exhibited no significant association between gender and periodontal disease. Whereas, [20] found that males had a greater frequency of periodontal diseases due to worse oral hygiene than female subjects.…”
Section: Resultssupporting
confidence: 84%
“…In this study, the age means of periodontal patients was 34.29±15.01 and ranged from 13 to 70 years. [21] showed that gingivitis was most common in the late adolescent age group (17)(18)(19)(20)(21)(22)(23)(24)(25), whereas chronic periodontitis was most common in the early elderly age group (46-55).…”
Section: Resultsmentioning
confidence: 99%
“…12, December, 2022 835 female both had high frequency of mild gingivitis with 43% and 50% respectively. Similarly, people everywhere suffer from periodontal disease, and although the elderly are more likely to be affected (17,18) . In adults, 50-100% of the population has gingivitis, according to the study conducted by Scannapieco FA, et al (19) .…”
Section: Discussionmentioning
confidence: 99%